PENGARUH ANTIFEEDANT EKSTRAK KULIT BATANG ANGSANA (Pterocarpus indicus Willd.) TERHADAP FEEDING STRATEGY WERENG COKLAT (Nilaparvata lugens Stal.) - Anggriani, Desi; Sumarmin, Ramadhan; Widiana, Rina (Pendidikan Biologi, 2013)
The Nilaparvata lugens Stal. is a harming parasitoid crop. Itâs difficult to eliminatebecause it have faster metamorphosis . This parasitoid can form blooming population in ashort time and destroy crop at all of growth phase. The aim of this research is to know theeffects of Antifeedant extrac of Pterocarpus indicus Willd. to Feeding Strategy Nilaparvatalugens Stal. This research used Completely Randomized Design ( CRD) with 4 treatment and10 replication. The treatment are concentration 0 %, 2.5 %, 5 % and 7.5 %. The data analysisby ANOVA and than continued with LSD. This experiment conducted in ZoologyLaboratory of FMIPA UNP at February 2013. Result shows that concentration 5 % activitysearching Nilaparvata lugens Stal. require time which fastest to other treatment, the activityof grounding treatment with concentration 2.5 % requiring time which quickly while atactivity of gathering treatment with concentration 7.5 % very effective to pursue to eat it.Can conclude that extract of angsana at concentration 5 % can be use antifeedant byNilaparvata lugens Stal.